Auditing practices in local governments : an international comparison - Ferry, Laurence; Ruggiero, Pasquale (Emerald Studies in public service accounting and accountability, 2022)
Public spending accounts for a significant share of national GDP and is perceived as a critically important way for overcoming periods of economic and social crisis, but is often criticised as inefficient and ineffective, giving raise to calls for new processes of reform. Because most public resources are raised through taxation from citizens and businesses, accountability and assurance are key in the democratic process, and auditing attempts to fulfil this public interest role. This in turn leaves public sector auditing under increasing public scrutiny and political pressure. Through a comparative analysis of the development of auditing practices in governments across the globe, Auditing Practices in Local Governments: An International Comparison provides a contemporary overview of public sector auditing practices at both local and state level. By focusing on countries which have experienced differing implementation processes, and which are characterised by different administrative and political cultures, the authors provide a comparative analysis of countries across the globe, including major European states, China, Australia, and New Zealand. Written by scholars and practitioners in the fields of public sector auditing, this first volume of Emerald Studies in Public Service Accounting and Accountability provides readers both researchers and practitioners with a thorough overview of international public sector auditing practice.